Analisis Pengaruh Pola Makan terhadap Gastritis Menggunakan Metode PRISMA - Syahfitri, Rizky Indah; Zahroh, Diajeng Ayu Sekar; Sinaga, Haryanti; Tanjung, Hazira Yulistia; Fidorova, Yolanda; Tumanggor, Suro Rahmadhona (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Gastritis occurs due to inflammation in the lining of the stomach that can cause pain. Gastritis is often referred to by the term "mag" which is characterized by a systemic infection of the stomach. The purpose of this study was to review several literature studies related to the influence of diet on gastritis disease. The method used in this study is Systematic Literature Review using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) which is carried out istematically with the correct protocol or following stages. This study revealed that thereis an influence of diet on the incidence of gastritis. An irregular diet such as rarely eating breakfast, rarely eating 3 times a day willmake it difficult for the stomach to adapt. If this happens over a long period of time, there will be an excess of stomach acid which causes the stomach mucosa to become irritated and gastritis arises. The main factors causing the large number of students who experience gastritis are irregular eating (not eating 3 times a day), often consuming fast food (junk food) because it is considered more practical, and stress due to the large number of college assignments. Keywords: Diet, Gastritis, College Students.